Peningkatan Prestasi Belajar Bahasa Arab Melalui Pembelajaran Berbasis Permainan Edukatif - Mar'atus Sholihah; Khairunnisa Khairunnisa; Daimah Daimah (Lembaga Riset dan Inovasi Almatani, 2026)
This study is motivated by the low level of students’interest in learning Arabic. The learning process, which tends to be conventional and monotonous, causes students to become easily bored, resulting in less optimal learning achievement. Therefore, a learning strategy is needed that can create a more engaging, interactive, and enjoyable learning environment through the implementation of educational games. This study aims to describe the implementation of educational games in Arabic language learning and their impact on students’ activeness and learning achievement. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews with teachers and students, and documentation of learning outcomes. Data analysis was conducted through several stages, namely data reduction, data display, and conclusion drawing to obtain an overview of students’ responses, levels of learning activeness, and changes in learning outcomes after the implementation of educational games. Based on the results of interviews with several students, it was found that learning using educational games in the form of flashcards made them more interested in participating in Arabic lessons. Students stated that this method helped them memorize vocabulary more easily and made the learning atmosphere more enjoyable. Keywords: Educational games, learning achievement, student activeness.